APOLOGETIKA DIALOGIS - Soleman Kawangmani (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2020)
Paguyuban Ngesti Tunggal (PANGESTU) is proliferating. PANGESTU claims that all religions are the same and are the essence of all formal religions' teachings. The postmodern context that upholds pluralism and truth relativism is challenging in proclaiming the Good News, especially for PANGESTU followers. Therefore, a new way of applying apologetics is needed to reach postmoderns. This study aimed to find the application of apologetics as a conversation model for the Good News in the PANGESTU mystical context. This study uses a qualitative approach. The method used is biblical hermeneutics and literature study. The researcher found